PRINSIP-PRINSIP KOMUNIKASI DALAM ALQURAN - Muhammad Jufri (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2015)
Authors are interested in one of the themes in the Qur'an as follows: Principles of Communication in this Alquran.Tema then be reviewed when something interesting in the Qur'an itself there are many verses that meaningful communication in a variety of konteksinya. Qur'an mention communication as one of human nature: Qaulan ma'rufa: words that are useful (Surah al-Baqarah / 2: 235), Qaulan Karima: words that treating others with respect (Surah Bani Israil/17: 23) Qaulan maysura: words are easily digested, concise and precise (Surah al-Kahfi/17: 28), Qaulan baligha: words are on target, not wishy-washy and plintat plintut (Surah al-Nisa / 4, 63) Qaulan layyina: gentle words, do not provoke (Surah Thaha/20: 44).